2016
DOI: 10.1111/resp.12737
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of peripheral non‐squamous non‐small cell lung cancer sampled by radial EBUS

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…Guiser et al . demonstrated that the molecular diagnosis of R-EBUS specimens was feasible for approximately 80% of patients with peripheral lung cancer 23 . However, the majority of these specimens were biopsy, rather than bronchial brushing, specimens, and the results from EGFR mutation analyses of brushing specimens were not compared with those from patient-matched histological samples.…”
Section: Discussionmentioning
confidence: 99%
“…Guiser et al . demonstrated that the molecular diagnosis of R-EBUS specimens was feasible for approximately 80% of patients with peripheral lung cancer 23 . However, the majority of these specimens were biopsy, rather than bronchial brushing, specimens, and the results from EGFR mutation analyses of brushing specimens were not compared with those from patient-matched histological samples.…”
Section: Discussionmentioning
confidence: 99%
“…This biological context could inherently prevent the interference of nontumor cells in heterogeneous specimens and, therefore, explain the sensitivity of RT‐PCR–based systems in the analysis of oncogenic mutations even with traditional Sanger sequencing . In another study, Guisier et al could achieve the molecular analysis in 15 of 27 patients (55.6%) for whom brushing alone was positive for malignancy and in 12 of 15 patients (80%) for whom biopsies alone were positive for cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the diagnosis of peripheral pulmonary lesions (PPLs) is still a challenge in clinical practice because of the difficulty of approaching them with standard bronchoscopy and because of the need to obtain large samples for pathological and molecular diagnoses . R‐EBUS–guided transbronchial biopsy using fluoroscopy has proven to be the most effective noninvasive techniques for the pathological diagnosis of peripheral lung nodules, and the molecular profiling of these samples seems to be feasible when biopsy or cell blocks can be performed …”
Section: Introductionmentioning
confidence: 99%
“…Even though our numbers are small, this finding is comparable to a study by Guisier et al . where multi‐gene molecular analysis could be performed in 80% of pulmonary lesions sampled by radial‐EBUS . However, despite the favourable rate, the 20% insufficiency rate for mutational analysis in radial‐EBUS is still much higher than that of EBUS TBNA of mediastinal lesions which is 4% .…”
Section: Discussionmentioning
confidence: 99%